Humoral and cellular response induced by a second booster of an inactivated SARS-CoV-2 vaccine in adultsResearch in context - Constanza Méndez; Hernán F. Peñaloza; Bárbara M. Schultz; Alejandro Piña-Iturbe; Mariana Ríos; Daniela Moreno-Tapia; Patricia Pereira-Sánchez; Diane Leighton; Claudia Orellana; Consuelo Covarrubias; Nicolás M.S. Gálvez; Jorge A. Soto; et al. (EBioMedicine, 2023)
Summary: Background: The Omicron variant has challenged the control of the COVID-19 pandemic due to its immuno-evasive properties. The administration of a booster dose of a SARS-CoV-2 vaccine showed positive effects in the immunogenicity against SARS-CoV-2, effect that is even enhanced after the administration of a second booster. Methods: During a phase-3 clinical trial, we evaluated the effect of a second booster of CoronaVac®, an inactivated vaccine administered 6 months after the first booster, in the neutralization of SARS-CoV-2 (n = 87). In parallel, cellular immunity (n = 45) was analyzed in stimulated peripheral mononuclear cells by flow cytometry and ELISPOT. Findings: Although a 2.5-fold increase in neutralization of the ancestral SARS-CoV-2 was observed after the second booster when compared with prior its administration (Geometric mean units p < 0.0001; Geometric mean titer p = 0.0002), a poor neutralization against the Omicron variant was detected. Additionally, the activation of specific CD4+ T lymphocytes remained stable after the second booster and, importantly, equivalent activation of CD4+ T lymphocytes against the Omicron variant and the ancestral SARS-CoV-2 were found. Interpretation: Although the neutralizing response against the Omicron variant after the second booster of CoronaVac® was slightly increased, these levels are far from those observed against the ancestral SARS-CoV-2 and could most likely fail to neutralize the virus. In contrast, a robust CD4+T cell response may confer protection against the Omicron variant. Funding: The Ministry of Health, Government of Chile, the Confederation of Production and Commerce, Chile and SINOVAC Biotech. NIH NIAID. The Millennium Institute on Immunology and Immunotherapy.